Quantification of atrial electrical heterogeneity via atrial electromechanical coupling - Tokatlı, Alptuğ; Yiğiner, Ömer; Kılıçaslan, Fethi; Uzun, Mehmet (Edizioni Minerva Medica, 2017)
[Abstract Not Available]
WOS: 000398129700022
PubMed ID: 28124874
Keywords: Atrial Electrical Heterogeneity; Atrial Electromechanical Coupling